Testosterone administration increases the size of womens' peripersonal space: An embodied index of social dominance - Masson, Catherine Jane (Department of Psychology, 2022)
Peripersonal space (PPS) is the space immediately surrounding the body, encoded by a specific frontoparietal network of multimodal neurons. Stimuli in PPS are represented in a body-part centred manner in terms of possibilities for action, and PPS representations function to facilitate defensive and/or approaching responses to stimuli. The size of PPS differs between individuals and contexts, with physical and psychological factors having a determining role on the size of PPS. For these reasons, PPS has been conceptualised as ‘the space of the bodily self'. In this study we investigated whether the dominance enhancing effects of testosterone may reflect in changes of the representation of PPS. We conducted a double-blind placebo-controlled within-subjects testosterone administration study in women (N=19) where participants performed a multisensory-integration task (a commonly used measure of PPS) while facing an unknown confederate. Results indicated that in comparison to placebo, the administration of testosterone caused a significant enlargement of participants' PPS, suggesting that testosterone caused participants to reflexively appropriate a larger space as their own. This effect was particularly pronounced in participants with higher trait anxiety, converging with other research which has shown that the dominance enhancing effects of testosterone administration can be particularly effective in anxious individuals. Results also indicated a multisensory-facilitation effect around the confederate, which was constant across testosterone and placebo conditions – confirming that the effect of testosterone was self-specific. The PPS boundary gradient was unchanged by testosterone. These findings suggest that an enlarged PPS may provide an embodied index of social dominance. Further, because PPS representations function to support approaching and/or defensive responses to the environment, an enlarged PPS due to raised testosterone may support the enhanced approach behaviour and vigilance to threat known to be conferred by testosterone.